Wahdat Al-Syuhud : Ahmad Sirhindi's Criticism on The Concept of Wahdat Al-Wujud Ibn 'Arabi - Muhammad Anang Firdaus; Rahmawansyah Sahib (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
This paper presents Sirhindi's criticism of the concept of Wahdat al-wujudIbn 'Arabi which is called Wahdatsyuhud. Comparing these two concepts will encounter obstacles, because the basis of thinking of Sufism for the two Sufis is different, IbnArabi emphasizes philosophical Sufism and Sirhindi emphasizes Sunni Sufism. However, the thoughts of both can be compared by presenting reasoning arguments that support constructing the two concepts as they are. This type of research uses descriptive qualitative, bibliographic data collection methods and data analysis uses comparative critical analysis with content analysis techniques. The results showed that Ibn 'Arabi in the doctrine of Wahdah al-wujud believes that the state of union with God is the peak stage and the highest point of attainment of a Sufi, tawhid - when understood in the sense of union with God - is the highest stage of Sufi life. However, Sirhindi sees tauhid - in the same sense - only as one of the suluk stages of a Sufi. The final stage is servitude and the final truth is difference. A different state after union which is completely different from that of pre-union is the highest state in the life of Sufism. The implementation of the research shows that intellectual dynamics is a characteristic of Muslim life, including the field of Sufism. Constructive discourse dialectics like this must be developed so as to enrich the treasures of Sufism in contemporary times.